Actions of Adenosine A2A Receptors on Synaptic Connections of Spiny Projection Neurons in the Neostriatal Inhibitory Network - Shindou, Tomomi; Arbuthnott, Gordon W; Wickens, Jeffery R (Journal of neurophysiology, 2008)
Department of Anatomy and Structural Biology, University of Otago, Dunedin, New Zealand; and Neurobiology Research Unit, Okinawa Institute of Science and Technology, Okinawa, Japan Submitted 15 November 2007; accepted in final form 12 February 2008 There is growing evidence that adenosine plays a crucial role in basal ganglia function, particularly in the modulation of voluntary movement. An adenosine-based treatment for Parkinson's disease shows promise in recent clinical studies. Adenosine A 2A receptors, the receptors involved in this treatment, are highly expressed in the neostriatum. Previous studies have suggested opposing actions of these receptors on synaptic transmission at striatal and pallidal terminals of the same spiny projection neurons, but the cells of origin of the intrastriatal terminals mediating these actions have not been identified. We used dual whole cell recordings to record simultaneously from pairs of striatal cells; this enabled definitive identification of the presynaptic and postsynaptic cells mediating the effects of A 2A receptors. We found that A 2A receptors facilitate GABAergic synaptic transmission by intrastriatal collaterals of the spiny projection neurons, consistent with their previously reported actions on synaptic transmission at pallidal terminals. This neuromodulatory action on lateral inhibition in the striatum may underlie, in part, the therapeutic efficacy of adenosine-based treatments for Parkinson's disease. Address for reprint requests and other correspondence: J. R. Wickens, Neurobiology Research Unit, Okinawa Institute of Science and Technology, Initial Research Project, 12-22 Suzaki, Uruma, Okinawa 904-2234, Japan (E-mail: wickensatoist.jp )